2019
DOI: 10.21873/anticanres.13584
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Speckle Tracking Echocardiography Changes Among Early-stage Breast Cancer Patients Three Years After Radiotherapy

Abstract: Background/Aim: Chest radiotherapy (RT) doubles late cardiac mortality. This study aimed to evaluate the evolution of cardiac changes in speckle tracking echocardiography during a three-year follow-up. Materials and Methods: This prospective study included 81 chemotherapy-naïve early-stage breast cancer patients who were evaluated at baseline, immediately after RT and three years after RT. Sixty-one patients had left-sided (LSBC) and 20 right-sided breast cancer (RSBC). Results: Global longitudinal strain (GLS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
(25 reference statements)
3
14
0
Order By: Relevance
“…This may explain the strongest decrease of the LS at the apical level as previously observed [6]. Moreover, in a previous study of patients with left-sided breast cancer [12], the segments with a significant strain reduction just after RT and 3 years post-RT were similar to those found in our study, particularly with regards to the mid-anterolateral segment and the apical-inferior segment. However, the association between LS decrease and cardiac dose is far to be clear and our correlations between LS decrease and doses to the different cardiac structures were low (under 0.3), as previously observed in several other studies [6,10,11].…”
Section: Location Of Ls Deteriorationsupporting
confidence: 91%
See 1 more Smart Citation
“…This may explain the strongest decrease of the LS at the apical level as previously observed [6]. Moreover, in a previous study of patients with left-sided breast cancer [12], the segments with a significant strain reduction just after RT and 3 years post-RT were similar to those found in our study, particularly with regards to the mid-anterolateral segment and the apical-inferior segment. However, the association between LS decrease and cardiac dose is far to be clear and our correlations between LS decrease and doses to the different cardiac structures were low (under 0.3), as previously observed in several other studies [6,10,11].…”
Section: Location Of Ls Deteriorationsupporting
confidence: 91%
“…Global longitudinal strain (LS) is often considered as an optimal parameter of deformation for the early detection of sub-clinical left ventricular dysfunction [4,5]. Many studies on early myocardial dysfunction after BC RT showed a significant decrease in global LS among left-sided breast cancer patients at different times post-RT, from few weeks to 3 years [6][7][8][9][10][11][12][13][14], whereas no measurable alteration of left ventricular ejection fraction (LVEF) was observed. Moreover, some previous works showed an association between the global LS decrease after BC RT and the mean heart dose or the mean left ventricular dose [15].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment protocols of patients with primary breast cancer most often include radiotherapy following breast-conserving surgery or mastectomy (2). Radiotherapy for breast cancer can be associated with acute and late toxicities (19)(20)(21). Being scheduled for radiotherapy may cause psychological distress that can lead to significant sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable linear regression analyses were performed to model the change in GLS and in left ventricular ejection fraction (LVEF) over three years, adjusting the models with the change in ST2 over three years, age, body mass index (BMI), laterality of BCa, aromatase inhibitor (AI) use and hypertension. Additionally, patients were divided into two groups: >15 and ≤ 15% relative change in global longitudinal strain (GLS) [ 24 ], a clinically meaningful change [ 24 , 25 ]. Differences between these groups were tested using multivariable logistic regression analysis, adjusting the model with the change in ST2 over three years, AI use, age and the mean dose to the left anterior descending coronary artery (LAD).…”
Section: Methodsmentioning
confidence: 99%